PERSPECTIVAS Y PROPUESTAS COMUNITARIAS EN LA VALORACIÓN DEL PATRIMONIO ARQUEOLÓGICO. UN CASO EN LA CIUDAD DE CASMA, COSTA NOR-CENTRAL DE PERÚ - Gamboa Velázquez, Jorge (2017)
In the last few decades archaeological perspectives have expanded to incorporate the involvement of different social groups and agendas. This contribution explores the results of the interaction between archaeological research and contemporary local initiatives that promote archaeological heritage in the coastal region of Ancash. To fulfill this objective I analyze the role of different stakeholders in the management of archaeological heritage in that part of northern Peru. The case study permits an assessment of how archaeology can contribute to the (re)construction of a regional Pre-Columbian history that is underrepresented in official discourses of Peruvian public education.